Tinjauan Islam dalam Berbagai Aspek Kehidupan Manusia di Era Modern - Ta’wil, Ta’wil; Harun, Hamzah; Aderus, Andi (Journal of Health, Education, Economics, Science, and Technology, 2025)
Islam is a religion followed by more than one billion people worldwide, significantly influencing various aspects of life, including theology, social, cultural, and political domains. This study aims to examine Islam from these multiple perspectives using a multidimensional approach. In the theological aspect, the study discusses the fundamental beliefs in Islam, such as tauhid, prophethood, and the afterlife. In terms of social and cultural aspects, it highlights how Islamic teachings interact with societal structures, education, and the role of women within society. Politically, the study explores the impact of Islamic teachings on governance systems and political dynamics in Muslim-majority countries. Additionally, this study distinguishes between Islam as a religion and Islam as religious interpretation, influenced by cultural and historical contexts. The findings of this study are expected to provide a deeper understanding of Islam in various aspects of life and encourage interfaith dialogue and respect for diversity in religious practices.